MODERN PROSPECTS FOR FINANCING THE MATERIAL AND TECHNICAL BASE OF HIGHER EDUCATION INSTITUTIONS (American Journal of Business Management, Economics and Banking, 2026)
This article examines modern prospects for financing the material and technical base of higher education institutions through a comparative analysis of official international datasets, national policy documents, and peer-reviewed literature. The study focuses on how systems fund laboratories, digital infrastructure, capital facilities, and research platforms. Evidence indicates that sustainable financing requires a blended structure combining core public funding, weighted allocation formulas, targeted capital grants, competitive project finance, moderate performance-based funding, and carefully governed revenue diversification. Cross-regional comparison demonstrates that public-dominant systems retain stronger baseline infrastructure security, while mixed public-private systems achieve higher spending but face volatility risks. Uzbekistan’s PF-58 reform package is examined as a significant example of explicit infrastructure-linked financing. The article concludes that the material and technical base should be financed through a portfolio model based on adequacy, transparency, full-cost logic, and lifecycle asset management.